Cisplatin induces chemoresistance through the PTGS2-mediated anti-apoptosis in gastric cancer. (November 2019) - Lin, Xiao-mian; Li, Song; Zhou, Chao; Li, Rong-zhen; Wang, Heng; Luo, Wu; Huang, Yi-shan; Chen, Lian-kuai; Cai, Jia-long; Wang, Tian-xiang; Zhang, Qi-hao; Cao, Hong; et al.
Highlights: PTGS2 and BCL2 are upregulated in cisplatin-resistant GC cells. PTGS2 regulates BCL2 expression through PGE2/EP4/MAPKs (ERK1/2, P38) axis. Cisplatin induces PTGS2 and BCL2 via ROS mediated NF-κB translocation. PTGS2 and BCL2 are positively correlated in human GC. PTGS2 inhibitor reverses the resistance to cisplatin via suppression of BCL2 expression in vivo . Abstract: It has been proposed that the aberrant expressions of the classical apoptosis-related genes and the subsequent decrease of apoptosis contribute to the development of cisplatin resistance in gastric cancer. However, little is known about the correlation and the molecular regulation mechanisms of cisplatin and the apoptosis-related gene expressions. Herein, we first identified the expressions of the anti-apoptotic BCL2 and the prostaglandin-endoperoxide synthase-2 (PTGS2) genes, which were abundant in the gastric carcinoma and associated with poor patient survival, were closely related with the resistance against cisplatin. Further investigations revealed that PTGS2 served as an essential mediator involved in the developing process of the resistance against cisplatin via mediating the inhibition effects of cisplatin on BCL2 expression. Mechanistically, cisplatin induced PTGS2 expression through ROS/NF-κB pathway. In addition, PTGS2 mediated cisplatin-induced BCL2 expression and subsequent resistance to apoptosis via PGE2/EP4/MAPKs (ERK1/2, P38) axis. Analysis of the clinical specimens demonstrated that PTGS2 and BCL2 were positively correlated in human gastric cancer. Moreover, in the xenograft models, inhibition of PTGS2 by celecoxib significantly augmented the cytotoxic efficacy of cisplatin in the resistant gastric cancer via suppression of PTGS2 and BCL2 expressions regulated by ERK1/2 and P38 signal axis, suggesting PTGS2 might be employed as an adjunctive therapeutic target for reversal of the chemoresistance in a subset of cisplatin resistant gastric cancer.